(untitled) (Bulletin KNOB, 2007)
How did people write about historical architecture in the MiddleAges? To what extent were they interested in ancient buildings? It is natural to assume that important buildings, for instance the great cathedrals, were also admired after the time of their realisation and that reports of this admiration have been preserved. However, such reports are probably rare. I do not know the reason of this, although I suppose that my research has not been sufficiently comprehensive. It is likely that there is more to be found in the extensive literary heritage of the Middle Ages, but who has the patience and possibility to tracé and read all the sources collected by, for instance, Max Manitius in his ‘Geschichte der Lateinischen Literatur des Mittelalters’ (1911-1931). Few buildings have been written about so much as the Hagia Sophia in Istanbul. This can be explained by the circumstance that famous authors have reported on it in great detail, among others Procopius and Paulus Silentiarius. What is found about ancient architecture in medieval chronicles is often just a single record, written in the manner of a minutes secretary. The first archaeologist who does make mention of ancient buildings, William Worcestre, limits his descriptions to stating the major measurements of the buildings ‘Itinerarium’ from 1478). Fortunately, there are a few sources from which a certain attachment to ancient architecture is evident. After the fire in the choir of Canterbury Cathedral in 1174 the clergy apparently preferred reconstruction of their choir, which dated from 1130. Consequently, they declared to be opposed to the idea of replacing the burnt choir by new construction. Similar sentiments also existed after the demolition of the Oudmunster in Utrecht in 1587. A fertile source that I have only superficially dealt with, are the reports of Jerusalem pilgrims and crusaders, in which some attention is indeed paid to the early Christian churches there. A research into the travelling literature in medieval Europe might yield more than 1 have been able to find so far.